Risk Factors of Catheter-Related Infection in Unplanned Extubation of Totally Implantable Venous-Accessportsin Tumor Patients. (27th September 2022) - Xu, Min; Deng, Lie; Zhu, Yanyi; Li, Yuanfang; Wang, Fan; Li, Hui; Zhou, Ying
Abstract : Background . Totally implantable intravenous ports (TIVAPs) are mostly used for long-term intravenous infusion therapy in cancer patients and can be left in the body for long periods of time for easy management, making them a simple and safe infusion device. Although the risks associated with long-term retention of fully implantable IV ports are less than those associated with other intravenous catheters, various complications may still occur at the time of implantation or during long-term use. Purpose . To provide a scientific basis for clinical reduction of implantable intravenous port-associated infection complications by studying the risk factors for catheter-associated infection complications in patients applying implantable intravenous ports. Methods . A retrospective study was conducted on oncology patients treated with TIVAP at our hospital between January 2017 and November 2021, with a review of patients who were unplanned for extubation. Their demographic data, underlying disease status, and surgery-related data were counted to summarize and analyze the complications and related influencing factors of implantation and postimplantation. Results . A total of 70 individuals with a mean age of 56.49 ± 12.19 years were included in the study. Among them, 39 were male and 64 had the highest percentage of epithelial tumors, followed by tumors of the lymphopoiesis system and mesenchymal tumors with 4 and 2 cases, respectively. Forty-eight of these patients did not have their ports removed as planned due to the occurrence of catheter-related hematogenous infections. In univariate analysis, BMI and neutropenia were risk factors for catheter-associated infections. In the multivariate analysis, BMI (OR = 1.38, 95% CI: 1.07–1.78, p = 0.013 ) was an independent risk factor for catheter-associated infections. Conclusions . The overall complication rate of fully implanted intravenous ports was high, but most complications improved with symptomatic management, and no deaths due to port complications were identified. Infection was the most common complication, with catheter-associated bloodstream infection being the most common cause of unplanned port extraction. Patients with a higher BMI were at high risk of developing implantable IV port-associated infections, which may be an independent risk factor for implantable IV port-associated infections.